Experiential Learning Model in Enhancing Prospective English Teachers` Teaching Competence - Heri Mudra; Toni Indrayadi (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2017)
This study aimed to describe the effectiveness of Experiential Learning (EL) model in improving prospective EFL teachers’ (PETs) teaching competence. The method of this study was Classroom Action Research (CAR) consisting of planning, observing, acting, and reflecting phases. There were two cycles needed in implementing EL to the twenty one EFL learners as the participants. The results revealed that each subcompetence in cycle I and cycle II was achieved in the following score: planning & preparation for learning (Mean in cycle I=2,8; Mean in cycle II=3,38), classroom management (Mean in cycle I=2,5; Mean in cycle II=2,95), delivery of instruction (Mean in cycle I=2,6; Mean in cycle II=2,90), and monitoring, assessment, and follow-up (Mean in cycle I=2,4; Mean in cycle II=2,95). It can be concluded that EL is effective in improving PETs’ teaching competence.